Study on the sedative effect and safety of oral midazolam combined with dexmedetomidine nasal drops in children during magnetic resonance imaging examination - Li, Yuancui; Lei, Rongzhu (Frontiers in Pediatrics, 2025)
BackgroundMagnetic resonance imaging (MRI) is a crucial non-invasive diagnostic tool for pediatric diseases, requiring patients to remain still, often with the use of sedatives. Midazolam and dexmedetomidine are commonly used for sedation in children, but their combined effect needs further study. This study aims to evaluate the safety and effectiveness of combining intranasal dexmedetomidine (ID) with oral midazolam (OM) in children undergoing MRI, and assess its clinical feasibility.MethodsA prospective, randomized controlled trial was conducted with 196 pediatric patients undergoing MRI from January 2022 to December 2023. Patients were randomly assigned to a control group (OM alone) or an observation group (OM + ID), with 98 cases each. Total sedation time, wake-up time, onset time, and adverse reactions were evaluated. Sedation effectiveness was assessed using the Ramsay Sedation Score.ResultsThe observation group had significantly longer total sedation time (P = 0.039) and higher one-time sedation success rate (P = 0.038) compared to the control group. The Ramsay score indicated better sedation effects in the observation group (P < 0.05). Adverse events were similar between groups and resolved with rest.ConclusionCombining ID with OM provides effective sedation for pediatric MRI, with an acceptable safety profile, supporting its use in clinical practice.